063 Differential Impact of Sleep Duration on Nocturnal Blood Pressure Dipping Between Men and Women. (3rd May 2021) - Bigalke, Jeremy; Greenlund, Ian; Nicevski, Jennifer; John-Henderson, Neha; Carter, Jason
Abstract: Introduction: There is growing evidence that poor sleep may have a greater impact on the development of cardiovascular complications in women compared to men. However, most studies that have evaluated the impact of sex on sleep insufficiencies and blood pressure (BP) have not utilized ambulatory BP, and often rely more heavily on subjective sleep diaries as opposed to objective sleep assessment. The purpose of this study was to examine the impact of sex on the relationship between objectively measured sleep and nocturnal BP dipping. We hypothesized that poor sleep would be associated with decreased nocturnal BP dipping, and that this association would be stronger in women. Methods: Total sleep time (TST) and sleep efficiency (SE) were monitored in fifty adults (31 men, 19 women; 36±3 years; 26±1 kg/m2) utilizing wrist actigraphy monitoring over the course of 5–14 days (Avg: 10±0 days). On a separate occasion, participants underwent a 24-hour ambulatory BP recording session. Independent samples T-tests were used to compare characteristics between sexes. Partial correlations controlling for age and BMI were utilized to probe relationships between sleep and nocturnal BP dipping. Results: TST and SE were not different between sexes. However, women exhibited reduced mean arterial pressure (MAP: 86±1 vs. 90±1 mmHg, P=0.026) compared to men. Partial correlation revealed a significant relationship between TST and the magnitude of nocturnal MAP dipping in the sample population (R = 0.460, P<0.001). When stratified by sex, this significant relationship persisted in men (R = 0.610, P<0.001), but not women (R = 0.108, P>0.05). In contrast, no relationship was observed between SE and nocturnal MAP dipping (R = -0.052, P>0.05) for the sample population. Similarly, SE did not correlate with nocturnal MAP dipping in men (R = -0.080, P>0.05) or women (R = 0.045, P>0.05). Conclusion: Contrary to our initial hypothesis, our results demonstrate that actigraphy-based TST is associated with nocturnal BP dipping in healthy men, but not women. This suggests a relation between impaired nocturnal BP regulation and habitual sleep duration, potentially predisposing men to an increased overall risk for cardiovascular complications. Support (if any): National Institutes of Health (HL-098676 and HL-122919)